Uso nocturno de perchas en dos especies de Anolis (Squamata: Polychrotidae) en un bosque Andino de Colombia (2007)
ABSTRACT: In this study we recorded the use of sleeping site by Anolis “anoriensis” and Anolis mariarum in two study sites located in the montane forest of the extreme northern of Cordillera Central, Colombia. We also tested the occurrence of spatial segregation between the two species. Furthermore, we estimated perch availability in both study sites. Anolis mariarum slept more frequently on shrubs (51%) than other kinds of perches (ferns, herbs, trees), but did so in proportion to their availability. Anolis “anoriensis” used different kinds of perches in each site, depending on the presence/absence of A. mariarum. Such variation in response to shrubs as sleeping perches by A. “anoriensis” suggests the existence of competition between the species when they are in syntopy